2021
DOI: 10.48550/arxiv.2112.13362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field-controlling patterns of sheared ferrofluid droplets

Shunichi Ishida,
Yaochen Yang,
Fanlong Meng
et al.

Abstract: We investigate how ferrofluid droplets suspended in a wall-bounded shear flow can organise when subjected to an external magnetic field. By tuning the magnitude of the external magnetic field, we find that the ferrofluid droplets form chain-like structures in the flow direction when the magnetic field is weak, while forming a crystal-like pattern in a strong magnetic field. We provide the phase diagram and the critical conditions for this chain-to-crystal transition, by applying both numerical simulations and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, Wang et al developed a 3D model based on volume of fluid method and predicted the prohibits the oil recovery when the magnetic field direction is transverse to the flow direction, which is in contrary to their experimental results, hinting the presence of other mechanisms (Wang et al, 2021), (Wang et al, 2020). Magnetic nanoparticles form temporal micro-structures when exposed to external disturbances of either magnetic fields (Robbes et al, 2011), (Tracy and Crawford, 2013) or shears (Ishida et al, 2021), as shown in Figure 15. These micro-structures can be permanentized by solidifying the fluid (Tracy and Crawford, 2013).…”
Section: Figure 14mentioning
confidence: 93%
“…However, Wang et al developed a 3D model based on volume of fluid method and predicted the prohibits the oil recovery when the magnetic field direction is transverse to the flow direction, which is in contrary to their experimental results, hinting the presence of other mechanisms (Wang et al, 2021), (Wang et al, 2020). Magnetic nanoparticles form temporal micro-structures when exposed to external disturbances of either magnetic fields (Robbes et al, 2011), (Tracy and Crawford, 2013) or shears (Ishida et al, 2021), as shown in Figure 15. These micro-structures can be permanentized by solidifying the fluid (Tracy and Crawford, 2013).…”
Section: Figure 14mentioning
confidence: 93%